Analisis Tingkat Literasi Artificial Intelligence Guru Dalam Media Pembelajaran Pada SDI Plus Darul Ulum Limo Depok - Tri Rahayu; Anita Muliawati; Rio Wirawan; Tjahjanto Tjahjanto; Bambang Triwahyono (Jurnal Ilmiah Matrik, 2025)
The acceleration of Artificial Intelligence (AI) technology in education requires teachers to have new competencies in integrating this technology into the learning process. At the elementary school level, AI literacy is crucial to support the implementation of the innovation-based Merdeka Curriculum. As a school committed to quality, SDI Plus Darul Ulum Limo Depok faces challenges in mapping the readiness of its teaching staff amidst diverse digital competency backgrounds. This study aims to analyze the level of AI literacy of teachers at SDI Plus Darul Ulum, covering cognitive, affective, technical, and pedagogical aspects, and to identify barriers to the use of AI as a learning medium. This study uses a descriptive quantitative approach. Data were collected through a structured questionnaire consisting of 15 statements with a Likert scale. The study respondents were all 30 teaching staff at SDI Plus Darul Ulum Limo Depok. Data analysis was conducted using descriptive statistics to determine the distribution of teacher literacy categories. The research findings show that the overall level of teacher AI literacy is in the Medium category (60%), with a small portion in the High (20%) and Low (20%) categories. Based on the aspect analysis, the highest score was achieved in the Affective aspect (4.10) which indicates teachers' positive attitudes and openness towards AI. However, the lowest score was found in the Pedagogical aspect (2.80), where teachers still experience difficulties in integrating AI into lesson plans (RPP) and teaching methods in the classroom.